(untitled) (International Journal of Engineering and Computer Science, 2017)
Cloud Computing, is the on-demand delivery of computing resources-everything from applications to traditional IT infrastructure(Data centers)-over the internet on the pay-for-use basis. Cloud Computing is the current need of the IT industry. Cloud Computing offers on demand internet based IT services like IaaS(Infrastructure as a Service), PaaS(Platform as a Service), DBaaS(DataBase as a Service), etc. With the exponential increase of the IT industry it is very difficult to maintain all the resources physically and hence the Cloud computing comes into the picture. Every IT industry requires data to be maintained and updated constantly and datacenters in the traditional IT has proved to be inefficient. Datacenters have huge unused resource which too requires capital. With the increase of data, it becomes very difficult to manage the data in the physical resources and hence companies use DBaaS (DataBase as a Service), where the data is saved on the servers which are not physically present at that location. Pre-configured and pre-defined structure of the database is present and hence deploying and maintaining the database becomes easy. With the deployment of DBaaS, analyzing the performance and optimization of the database is much better than doing the same in physical database.